Inflammasome activation in airway epithelial cells after multi-walled carbon nanotube exposure mediates a profibrotic response in lung fibroblasts - Hussain, Salik (BioMed Central, 2014)
BACKGROUND: In vivo studies have demonstrated the ability of multi-walled carbon nanotubes (MWCNT) to induce airway remodeling, a key feature of chronic respiratory diseases like asthma and chronic obstructive pulmonary disease. However, the mechanism leading to remodeling is poorly understood. Particularly, there is limited insight about the role of airway epithelial injury in these changes. OBJECTIVES: We investigated the mechanism of MWCNT-induced primary human bronchial epithelial (HBE) cell injury and its contribution in inducing a profibrotic response. METHODS: Primary HBE cells were exposed to thoroughly characterized MWCNTs (1.5-24 μg/mL equivalent to 0.37-6.0 μg/cm(2)) and MRC-5 human lung fibroblasts were exposed to 1:4 diluted conditioned medium from these cells. Flow cytometry, ELISA, immunostainings/immunoblots and PCR analyses were employed to study cellular mechanisms. RESULTS: MWCNT induced NLRP3 inflammasome dependent pyroptosis in HBE cells in a time- and dose-dependent manner. Cell death and cytokine production were significantly reduced by antioxidants, siRNA to NLRP3, a caspase-1 inhibitor (z-WEHD-FMK) or a cathepsin B inhibitor (CA-074Me). Conditioned medium from MWCNT-treated HBE cells induced significant increase in mRNA expression of pro-fibrotic markers (TIMP-1, Tenascin-C, Procollagen 1, and Osteopontin) in human lung fibroblasts, without a concomitant change in expression of TGF-beta. Induction of pro-fibrotic markers was significantly reduced when IL-1β, IL-18 and IL-8 neutralizing antibodies were added to the conditioned medium or when conditioned medium from NLRP3 siRNA transfected HBE cells was used. CONCLUSIONS: Taken together these results demonstrate induction of a NLRP3 inflammasome dependent but TGF-beta independent pro-fibrotic response after MWCNT exposure.